Factors Related to Giving Hb0 Immunization at Batu Anam Health Center, Simalungun - Sondang Sidabutar; Srirahma Friani; Riada Marenny Pasaribu (Humanistic Network for Science and Technology (HNST), 2021)
More than 11 million people with Hepatitis-B in Indonesia, with a low prevalence of hepatitis B, most of the sufferers were aged 20-40 years, while in countries with a high prevalence of hepatitis B, the majority of people with hepatitis B were children.. The purpose of this study was to determine the factors associated with giving Hb0 immunization to infants. The design of research was analytical. The study population was all mothers who had babies 0-7 days in Batu Anam Community Health Center. The sample size was 60 people. The research results were obtained based on the provision of Hb0 immunization, it was known that the majority of respondents were not given the Hb0 immunization as many as 33 respondents (55.0%) and the minority of respondents were given the Hb0 immunization as many as 27 respondents (45.0%) and it could be concluded that there was a relationship between education, work, number of children, knowledge, helpers. delivery, delivery assistance and family support for Hb0 immunization in infants. It is hoped that this research can become input for health workers to improve the quality of health services and education as well as information about Hb0 immunization in infants by providing counseling. Keywords: Hb0 immunization; infants